Evaluative inquiry for learning in organizations - Preskill, Hallie S. (Sage Publications, 1999)
'Evaluative Inquiry for Learning in Organizations' shows a way to conduct evaluative inquiry in any kind of organisation. The approach is data-based, and the focus on use within organisations.